Regulation of Jealousy Protest in the Context of Reunion Following Differential Treatment. (30th April 2013) - Hart, Sybil L.; Behrens, Kazuko Y.
Abstract : Emotion regulation strategies and variation in their presentation were explored toward understanding infants' responses during reunion with mother (Re) following baseline mother–infant interaction (Bl) and differential treatment (DT) episodes. Correlation analyses revealed cohesion among distress and mother‐directed touch and proximity‐seeking during DT and Re, mother‐directed gaze during DT, and resistance during Re. The association between mother‐directed gaze during DT and distress during Re suggests that visual inattention during DT serves as a regulatory strategy. Overall, these linkages yield expanded understanding of jealousy protest as a constellation of responses that endures beyond the eliciting condition and includes regulatory behaviors. Cross‐context comparisons revealed that distress was lower during Re than during DT, but not as low as Bl, suggesting that DT poses challenge to interactive repair. Inquiry into individual variation revealed that distress during Re was augmented in laterborn males and with risk influences of dysregulated fear, and maternal insensitivity and hostility. Conversely, maternal depression was associated with less distress; later judgment as insecure, especially insecure‐avoidance, was associated with less mother‐directed behaviors. These findings suggest that dysregulation following DT is indicated by both resistance and passivity. In sum, the results highlight emotion regulation as a powerful framework for addressing recovery following DT.